UPAYA MENINGKATKAN HASIL BELAJAR MATA PELAJARAN SEJARAH MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) PADA SISWA KELAS X¹ DI SMA N 1 PUSAKO KECAMATAN PUSAKO KABUPATEN SIAK - Yulia Sari; Kamarrudin Oemar; Asril ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The implementation of education through the teaching and learning process is basically the core of the overall education, in which teachers as the main role holder. Teacher as a learner who is directly involved in the learning process, work to create learning conditions that can make students learn optimally to obtain satisfactory academic achievement. The purpose of this study was 1) to determine the activity of teachers using cooperative learning model two stay two stray 2) to determine the activity of students using cooperative learning model type of two stay two stray 3) to determine the effect of cooperative learning model type of two stay two stray to the results of study subjects in the history of X¹ class SMA Negeri 1 Pusako Pusako Subdistrict Siak. In this study, using a quantitative method in which it will provide full information so useful to science. The results of this study indicate that the application of cooperative learning model Two Stay Two Stray can improve the quality of the learning process both from the teachers and students. Cooperative learning model type Two Stay Two Stray can improve learning outcomes in the subjects of history X¹ class SMA Negeri 1 Pusako. This is evidenced by the increase in pre PTK learning outcomes with an average value of 66.17 increased to 70.73 in the first cycle and 85.44 in the second cycle.Key Words: Class Action Research, Two Stay Two Stray, Student Results